Validation of the fear of COVID-19 scale in a central Balkan country - Serbia - Zivkovic Zaric, Radica; Zaric, Milan; Canovic, Petar; Jankovic, Slobodan; Stojadinovic, Milorad; Zornic, Nenad; Nesic, Jelena; Spasic, Marko; Jovanovic, Dalibor; Jug, Martina; Jakovljevic, Stefan; Pejcic, Ana (Frontiers in Public Health, 2022)
Introduction. High levels of fear of COVID-19 may be associated with increased levels of stress, anxiety, and depression, as well as decreased resilience and life expectancy. Objective. This study aimed to translate and confirm the Serbian version of the Fear of COVID-19 scale as well as to investigate its psychometric properties. Methods. The translation and intercultural adaptation of the Fear of COVID-19 scale was performed by the leading standard of the International Society for Pharmacoeconomics and Outcome Research. When the distribution was normal, the Kolmogorov-Smirnov test was used. The reliability of the Serbian version of FCV-19S was tested by measuring the internal consistency through the value of Cronbach's alpha. Results. The original version of the Fear of COVID-19 scale was tested on a sample of 256 subjects with a mean age of 25.38 ± 12.47. The Cronbach's alpha value was 0.864. We divided the scale by the split-half method (Spearman-Brown), and the value of the coefficient for the questionnaire as a whole was 0.882. Conclusion. The validated version of the scale in Serbia complements versions available in other cultures and other languages and facilitates global studies related to mental health during the COVID-19 pandemic.